2008
DOI: 10.1161/circulationaha.107.740498
|View full text |Cite
|
Sign up to set email alerts
|

Glucometrics in Patients Hospitalized With Acute Myocardial Infarction

Abstract: Background-Hyperglycemia on admission is associated with an increased mortality rate in patients with acute myocardial infarction. Whether metrics that incorporate multiple glucose assessments during acute myocardial infarction hospitalization are better predictors of mortality than admission glucose alone is not well defined. Methods and Results-We evaluated 16 871 acute myocardial infarction patients hospitalized from January 2000 to December 2005. Using logistic regression models and C indexes, 3 metrics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
282
4
15

Year Published

2008
2008
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 351 publications
(317 citation statements)
references
References 57 publications
(23 reference statements)
12
282
4
15
Order By: Relevance
“…In our series, glucose values (when corrected for HOMA index) are independently associated with in-ICCU BMI body mass index, AMI acute myocardial infarction, LVEF left ventricular ejection fraction, PCI percutaneous coronary intervention, Hb A1c glycated hemoglobin, NT-pro-BNP N terminal-pro-brain natriuretic peptide, eGFR estimated glomerular filtration rate * Fisher's exact test Acta Diabetol mortality (thus confirming previous data by others and us) [4][5][6][7][8][9][10][11] and with in-ICCU complications. The complexity of the glycometabolic response to stress during acute myocardial infarction, as well as the scarcity of data on this topic, can be inferred by still existing controversies on how to manage increased glucose values in patients with acute coronary syndromes.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our series, glucose values (when corrected for HOMA index) are independently associated with in-ICCU BMI body mass index, AMI acute myocardial infarction, LVEF left ventricular ejection fraction, PCI percutaneous coronary intervention, Hb A1c glycated hemoglobin, NT-pro-BNP N terminal-pro-brain natriuretic peptide, eGFR estimated glomerular filtration rate * Fisher's exact test Acta Diabetol mortality (thus confirming previous data by others and us) [4][5][6][7][8][9][10][11] and with in-ICCU complications. The complexity of the glycometabolic response to stress during acute myocardial infarction, as well as the scarcity of data on this topic, can be inferred by still existing controversies on how to manage increased glucose values in patients with acute coronary syndromes.…”
Section: Discussionsupporting
confidence: 81%
“…In patients with ST-elevation myocardial infarction (STEMI), hyperglycemia is common and, though frequently untreated, associated with an increased risk of death [4][5][6][7]. In these patients, increased glucose values hold a prognostic role when measured not only on admission [4] but also throughout hospital stay [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Glucose values and acute insulin resistance have been investigated in various acute cardiac conditions [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with ST elevation myocardial infarction (STEMI), hyperglycemia is common, and, though frequently untreated, associated with an increased risk of death [1][2][3][4][5]. In these patients, increased glucose values hold a prognostic role when measured not only on admission [1], but also throughout hospital stay [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent observational study of glucometrics in patients hospitalized with acute myocardial infarction found that the simple mean of each patient's glucose values over the entire hospitalization was as predictive of in-hospital mortality as the HGI or the time-averaged glucose (AUC for all glucose values). 4 In this study, metrics derived from glucose readings for the entire hospitalization were more predictive than those based on the first 24 or 48 hours or on the admission glucose.…”
Section: Hyperglycemic Indexmentioning
confidence: 65%